2016
DOI: 10.1038/srep24560
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Population Responses in the Somatosensory Cortex of Alzheimer’s Disease Model Mice

Abstract: Alzheimer’s disease (AD) is the most common form of dementia. One of the neuropathological hallmarks of AD is the accumulation of amyloid-β plaques. Overexpression of human amyloid precursor protein in transgenic mice induces hippocampal and neocortical amyloid-β accumulation and plaque deposition that increases with age. The impact of these effects on neuronal population responses and network activity in sensory cortex is not well understood. We used Voltage Sensitive Dye Imaging, to investigate at high spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 104 publications
2
17
0
1
Order By: Relevance
“…Therefore, the hyperexcitability seen in the J20-AD mouse, APP/PS1 mice and younger AD-patients may be related to the brains initial reaction to the emerging presence of Aβ oligomers, or that of aberrant APP processing. Whisker deflection in APP/PS1 mice also resulted in much higher neural responses in the cortex, also supporting our findings 28 . In our study, the observed enhanced neural activity couples well with the enhanced haemodynamic responses, suggesting that neurovascular coupling in the J20-AD mouse is intact and functioning well at this younger age of 6-9m.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the hyperexcitability seen in the J20-AD mouse, APP/PS1 mice and younger AD-patients may be related to the brains initial reaction to the emerging presence of Aβ oligomers, or that of aberrant APP processing. Whisker deflection in APP/PS1 mice also resulted in much higher neural responses in the cortex, also supporting our findings 28 . In our study, the observed enhanced neural activity couples well with the enhanced haemodynamic responses, suggesting that neurovascular coupling in the J20-AD mouse is intact and functioning well at this younger age of 6-9m.…”
Section: Discussionsupporting
confidence: 90%
“…A study in APPswe mice used whisker stimulation and voltage sensitive dye imaging to correlate Aβ plaques with abnormal neural population responses in the somatosensory cortex and with reduced cortical synchronization during spontaneous activity 96 . This matches our observation of a dysfunctional TPN.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if both motor deficits and anxiety‐like behaviour are unlikely in the 5xFAD mice, changes in whisker behaviour may be due to alterations in sensory processing. It has been suggested that 5xFAD mice might have hypersensitive whiskers due to a reduction of inhibition in the barrel cortex, with the barrel cortex producing large amplitude neural responses with a broad spatial spread following a whisker deflection . It may be that whisker signals are not processed efficiently in the cortex, therefore, their exploratory movements increase to gain more sensory information; or that they are over‐sensitive, so decrease whisker angular positions in order to reduce the force applied to the whisker from an object contact.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that 5xFAD mice might have hypersensitive whiskers due to a reduction of inhibition in the barrel cortex, 11 with the barrel cortex producing large amplitude neural responses with a broad spatial spread following a whisker deflection. 44 It may be that whisker signals are not processed efficiently in the cortex, therefore, their exploratory movements increase to gain more sensory information; or that they are over-sensitive, so decrease whisker angular positions in order to reduce the force applied to the whisker from an object contact. Further investigations into whisker object contacts and forces in 5xFAD mice might help to tease apart these hypotheses (ie, Campagner et al 45 ).…”
Section: Discussionmentioning
confidence: 99%